Discursive analysis of the emergence of the concept of habitat in the framework of International Organizations - Sesma, María Inés (2023)
The following article intends to show how, why and for what the discursive category of habitat, was and is configured by international organizations according to dominant notions, within the framework of the development project. To do this, the different themes that are made of the habitat in three major periods are shown based on the Habitat Conferences held by the United Nations Organization (HABITAT I, II and III), in order to find in each of these the discursive particularities that shaped the “regimes of truth” around the habitat. For the analysis, the theoretical and analytical proposal of Michel Foucault regarding the discourse and the contributions of Arturo Escobar on the concept of development are taken. Based on the hypothesis that these dominant notions of habitat can be grouped under the notion of “urban habitat”, as that space where “legitimate” ways of inhabiting converge, the article invites us to think from a critical perspective about the meaning and the implication of addressing the habitat from dominant discourses.